What is life?:with Mind and Matter and Autobiographical Sketches - Erwin Schrödinger (Cambridge University Press, 1992)
Nobel laureate Erwin Schrodinger\\\'s What is Life? is one of the great science classics of the twentieth century. A distinguished physicist\\\'s exploration of the question which lies at the heart of biology, it was written for the layman, but proved one of the spurs to the birth of molecular biology and the subsequent discovery of the structure of DNA. The philosopher Karl Popper hailed it as a \\\'beautiful and important book\\\' by \\\'a great man to whom I owe a personal debt for many exciting discussions\\\'. It appears here together with Mind and Matter, his essay investigating a relationship which has eluded and puzzled philosophers since the earliest times. Schrodinger asks what place consciousness occupies in the evolution of life, and what part the state of development of the human mind plays in moral questions. Brought together with these two classics are Schrodinger\\\'s autobiographical sketches, published and translated here for the first time. They offer a fascinating fragmentary account of his life as a background to his scientific writings, making this volume a valuable additon to the shelves of scientist and layman alike.